A reflection on the socio-legal perspectives of islamic banking in Nigeria (2015)
The introduction of Islamic banking model into the Nigeria banking sector by the Central Bank of Nigeria had generated a lot of controversies and will continue to be a source of concern for a very long time. The grouse of people at the time was due to the close linkage between Islamic banking practice and the Islamic religion ethical value against charging interest in financial transactions. For instance, people argued among others that the introduction is a clever attempt to Islamize the country. Of course, the fear appeared somewhat justified due to the utterances in some quarters, mostly from Muslim Scholars and Clerics, worst still, the sudden incursion of Boko Haram in the Northern part of Nigeria. However, having examined, with deep reflection, the close relationship between Islamic banking system and Islamic religion as well as the perspectives of traditional as well as Christian religions on charging interest in financial transactions; this paper aims to examine various issues raised by people consequent to the introduction of Islamic banking into the Nigerian banking sector. To enhance a full understanding of Islamic banking, the paper traces the evolution and various concepts and principles which characterizes Islamic banking system, the challenges and prospects inherent in the system, the statutory and constitutional frameworks for the operation of the system. This paper also discusses the position of Christian and traditional religions on charging of interest in financial transactions. The ultimate aim of the paper is to foster mutual understanding on the continued existence of Islamic Banking system in the banking sector in Nigeria.